The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/625050
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Signaling Factors in Brain Ischemia/Reperfusion Rats: Differential Modulation Pattern between Single‐Time and Multiple Electroacupuncture Stimulation

Abstract: Electroacupuncture (EA) treatment has been widely used for stroke-like disorders in traditional Chinese medicine. However, the underlying mechanisms remain unclear. Our previous studies showed that single-time EA stimulation at “Baihui” (GV 20) and “Shuigou” (GV 26) after the onset of ischemia can protect the brain against ischemic injury in rats with middle cerebral artery occlusion (MCAO). Here, we further investigated the differential effects between multiple EA and single-time EA stimulation on ischemic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…These data suggest that MEK1 is activated in the hippocampus contralateral to the nerve injury side following four times of EA intervention, and this increase in MEK1 activity may initiate a cumulative effect of EA treatment. Previously reported gene screening results suggest that the discrepancy between the effects of multiple and single EA treatments on brain ischemia/reperfusion are possibly caused by their differential modulation on gene expression, such as brain-derived neurotrophic factor and signal transducer-related genes [4]. This proposal is consistent with our data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data suggest that MEK1 is activated in the hippocampus contralateral to the nerve injury side following four times of EA intervention, and this increase in MEK1 activity may initiate a cumulative effect of EA treatment. Previously reported gene screening results suggest that the discrepancy between the effects of multiple and single EA treatments on brain ischemia/reperfusion are possibly caused by their differential modulation on gene expression, such as brain-derived neurotrophic factor and signal transducer-related genes [4]. This proposal is consistent with our data.…”
Section: Discussionsupporting
confidence: 92%
“…Acupuncture therapy, a method of traditional Chinese medicine, has received worldwide attention as a strategy to relieve pain [13]. Clinical practice demonstrates that multiple sessions of acupuncture treatment (not a single session) may induce an obvious analgesic effect [4–6]. However, the number of acupuncture treatment sessions required for effective pain relief is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Protein samples (15 μ g/lane) from different groups were electrophoresed on 10% SDS–polyacrylamide gel and transferred to the polyvinyl difluoride membrane (Bio‐Rad, Hercules, CA, USA) as the method described . Peroxidase activity was visualized with an enhanced chemiluminescence substrate system (ECL; Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…EA intervention is reported to suppress ischemia-elicited astrocyte activation and reduce the expression of GMF. Thus, it is speculated that EA might inhibit astroglial activation via decreasing GMF (Wang et al, 2014) (as shown in Table 1).…”
Section: Literature Research Criteriamentioning
confidence: 99%